Kajian Pemerintahan yang Partisipatif Dalam Pemeliharaan Taman di Kota Kupang (Model Kolaborasi Pemerintah, Korporasi dan Masyarakat Sipil) - William Djani (Jurnal Inovasi Kebijakan, 2021)
. This research is strategically used as a solution instrument for crucial issues related to participatory governance in the management of City Parks, especially in the City of Kupang. By using relevant references, it produces differentiation and new values ??of City Park management in the development of scientific repertoire in the field of Urban Policy. Therefore, the principle of participatory governance needs to be applied. The problem is how to involve the community in maintaining the City Park? The purpose of this research is to know and analyze Participatory Governance in Park Maintenance in Kupang City. Thus, the current focus of the study on urban parks lies in the aspect of infrastructure, and how local regulations support in providing space for partnerships, as well as how the awareness and willingness of civil society, as well as corporations to participate in the maintenance of city parks, apart from finding a form of cooperation that appropriate and effective in the maintenance of city parks. The results of the study provide two recommendations, namely: (1) the potential of civil society and corporations managing city parks, and (2) forms of cooperation between potential managers (civil society, corporations) and the Kupang City Government. Meanwhile, the long-term goal, in particular, is to propose improvements to local government policies in building a collaboration model between the Kupang city government and the community that ensures the beauty of city parks is maintained. To achieve this goal, the research team reviewed the theories and concepts of participatory governance using a public policy perspective. The goal is that this perspective can focus on research and analysis frameworks that are appropriate, relevant, applicable, measurable with scientifically justifiable methodologies. The results of the study show that many city parks that have been built are expected to be well maintained so that they have attractiveness, and ensure the comfort of visitors to enjoy their beauty. However, the Government certainly has a number of limitations in its maintenance so that it requires continuous improvement. The results of this study were derived as new concepts of participatory government based on the urban social context so that in the end they were able to make a concrete contribution to the achievement of the City Park development program strategy as a green open space. Therefore, the recommendation put forward in this study is the need to build a synergistic actor relationship in the management of City Parks that is supported by adequate regulations.